Endoscopic techniques for diagnosis and correction of complications after retroperitoneal pancreas transplantation - A. V. Pinchuk; I. V. Dmitriev; Yu. S. Teterin; A. G. Balkarov; N. V. Shmarina; R. V. Storozhev; Yu. A. Anisimov; A. S. Kondrashkin (Трансплантология (Москва))
Relevance. Timely diagnosis and treatment of postoperative complications after pancreas transplantation is an actual problem of modern clinical transplantation. Purpose. The assessment of the endoscopy potential for the diagnosis and correction of postoperative complications after pancreas transplantation. Materials and methods. Since October 2011, simultaneous retroperitoneal pancreas-kidney transplantation has been performed in 27 patients. In 8 cases, the use of endoscopic techniques allowed a timely identification and treatment of the complications occurred. Conclusions. Endoscopic techniques proved to be highly efficient in the diagnosis and treatment of surgical complications and immunological impairments after retroperitoneal pancreas transplantation.